Acute alcohol-induced pancreatic injury is similar with intravenous and intragastric routes of alcohol administration - Schneider, Lutz; Dieckmann, Ralf; Hackert, Thilo; Gebhard, Martha-Maria; Werner, Jens (Pancreas, 2014)
Objectives - Five percent of alcoholics develop an acute pancreatitis (AP). The mechanism leading to pancreatic injury is not yet understood. Microcirculatory disorders seem to play a pivotal role. The objective of this study was to compare alcoholic pancreatic injury in response to intravenous and intragastric routes of alcohol administration. - Methods - Alcohol was applied in rats intravenously (IV) or gastric via a surgical implanted feeding tube (IG). Serum alcohol concentration was maintained between 1.5‰ and 2.5‰. Four subgroups (n = 6/group) were examined in the IV/IG arm and compared with healthy controls. Pancreatic microcirculation, enzyme levels, and morphological damage were assessed after 3, 6, 12, and 24 hours. - Results - Microcirculatory analysis showed significantly disturbed pancreatic perfusion and increased adherent leukocytes in IV and IG animals. In IV and IG groups, serum amylase was increased without morphological signs of AP compared with healthy controls. - Conclusions - Alcohol application does not induce AP in rodents, but impairs pancreatic microcirculation irrespectively of the application route. Intravenous application is commonly used and shows no disadvantages compared with the physiological intragastric application form. Therefore, the intravenous route offers a valid model, which mimics the physiological process for further studies of the influence of acute alcohol intoxication on the pancreas.
Gesehen am 02.09.2020